THE INFLUENCE OF NURSING TECHNICIANS' PERCEPTION OF WORKPLACE SAFETY ON THEIR ADHERENCE TO INFECTION CONTROL PRACTICES IN SAUDI HEALTHCARE SETTINGS - Al-Hanouf Julaidan Qunafid Al-Dhafiri, Amani HamdanHadi AlDhafeere, Eman krboosh hazza Aldufairy, Aiydah Aiyed A Aldhafeeri, Abeer Saad Raheel Al-Shammari, Magda Al-Shawi Samdan Al-Ruwaili, (Chelonian Research Foundation, 2022)
Nursing technicians play a crucial role in maintaining infection control practices in healthcare settings. Their perception of workplace safety can significantly influence their adherence to these practices. This study aims to investigate the relationship between nursing technicians' perception of workplace safety and their adherence to infection control practices in Saudi healthcare settings. A mixed-methods approach was employed, involving a survey and semi-structured interviews with nursing technicians across various healthcare facilities in Saudi Arabia. The findings reveal that nursing technicians who perceive their workplace as safe are more likely to adhere to infection control practices consistently. Factors such as organizational support, training, and availability of personal protective equipment contribute to their perception of workplace safety. The study also identifies challenges faced by nursing technicians in adhering to infection control practices, including workload, time constraints, and lack of resources. The findings highlight the importance of fostering a culture of safety and providing adequate support to nursing technicians to enhance their adherence to infection control practices. Recommendations for healthcare organizations and policymakers include providing regular training, ensuring the availability of necessary resources, and promoting open communication and feedback channels. By addressing the factors influencing nursing technicians' perception of workplace safety, healthcare organizations can improve infection control practices and ultimately enhance patient safety and outcomes. Keywords: nursing technicians, workplace safety, infection control practices, adherence, Saudi Arabia